Seed system security assessment: Haiti - International Center for Tropical Agriculture; Ministère de l’Agriculture, des Ressources Naturelles et du Développement Rural, Haiti; University of East Anglia; Food and Agriculture Organization of the United Nations; World Concern; Save the Children; ACDI/VOCA; World Vision; Catholic Relief Services (International Center for Tropical Agriculture, 2010)
A Seed System Security Assessment (SSSA) was carried out in Haiti in May-June 2010. The work assessed the impact of the 12 January 2010 earthquake on households and agricultural livelihoods, including possible changes in assets, land holdings, labor availability, income generation activities, crop profiles and seed use. The work also analyzed acute seed security issues, monitoring farmers' seed procurement strategies and examining the effects of any aid given. As a third thrust, the SSSA looked at chronic seed security problems, including those related to seed/grain markets, agricultural product transformation and access to modern varieties. Hence the foci included 'very short term', as well as short- and medium-term issues.